Core-crosslinked, temperature- and pH-responsive micelles: design, physicochemical characterization, and gene delivery application. Issue 46 (30th September 2021) - Leer, Katharina; Cinar, Gizem; Solomun, Jana I.; Martin, Liam; Nischang, Ivo; Traeger, Anja
Abstract : Stimuli-responsive block copolymer micelles can provide tailored properties for the efficient delivery of genetic material. Abstract : Stimuli-responsive block copolymer micelles can provide tailored properties for the efficient delivery of genetic material. In particular, temperature- and pH-responsive materials are of interest, since their physicochemical properties can be easily tailored to meet the requirements for successful gene delivery. Within this study, a stimuli-responsive micelle system for gene delivery was designed based on a diblock copolymer consisting of poly( N, N -diethylacrylamide) (PDEAm) as a temperature-responsive segment combined with poly(aminoethyl acrylamide) (PAEAm) as a pH-responsive, cationic segment. Upon temperature increase, the PDEAm block becomes hydrophobic due to its lower critical solution temperature (LCST), leading to micelle formation. Furthermore, the monomer 2-(pyridin-2-yldisulfanyl)ethyl acrylate (PDSAc) was incorporated into the temperature-responsive PDEAm building block enabling disulfide crosslinking of the formed micelle core to stabilize its structure regardless of temperature and dilution. The cloud points of the PDEAm block and the diblock copolymer were investigated by turbidimetry and fluorescence spectroscopy. The temperature-dependent formation of micelles was analyzed by dynamic light scattering (DLS) and elucidated in detail by an analytical ultracentrifuge (AUC), which provided detailed insights into the solution dynamics between polymers and assembled micelles as a function of temperature. Finally, the micelles were investigated for their applicability as gene delivery vectors by evaluation of cytotoxicity, pDNA binding, and transfection efficiency using HEK293T cells. The investigations showed that core-crosslinking resulted in a 13-fold increase in observed transfection efficiency. Our study presents a comprehensive investigation from polymer synthesis to an in-depth physicochemical characterization and biological application of a crosslinked micelle system including stimuli-responsive behavior.